Hubungan Pemakaian Sepatu Hak Tinggi Terhadap Plantar Heel Pain Pada Sales Promotion Girl Oppo Di Plaza Millenium - Clara Sherly Oktavia Ketaren; Anggriani Anggriani; Roni Gunawan (LPPM STIKES Siti Hajar dan Insight Power, 2022)
SPG is one of the jobs required to use high heels at work. SPG usually wears high heels to support their appearance and attract attention so that consumers are interested in buying the goods they offer. Wearing high heels causes plantar heel pain because high heels push the foot into a plantarflexed position, forcing the muscles and tendons to work harder to compensate. The medial gastrocnemius muscle fascicle shortens and the Achilles tendon becomes stiffer due to the length of time the compensation takes. Objective: To find out whether there is a relationship between the use of high heels and plantar heel pain at Sales Promotion Girl Oppo at Plaza Millennium. Methods: This research is an analytic observational type with a cross-sectional design. Determination of the sample using purposive sampling that meets the inclusion and exclusion criteria with a sample of 38 respondents. Researchers took data in the field by providing an observation sheet measuring plantar heel pain (VAS) and measuring heel height with the midline. Results: The results of the Pearson test showed that the significance value or p value = 0.000 (p <0.05). Conclusion: There is a relationship between the use of high heels on plantar heel pain at Sales Promotion Girl OPPO at Plaza Millenium.. .Keywords: High heels, plantar heel pain